Central nervous system aspergillosis in immunocompetent patients: Case series and literature review. Issue 44 (30th October 2020) - Ma, Yubao; Li, Wanjun; Ao, Ran; Lan, Xiaoyang; Li, Yang; Zhang, Jiatang; Yu, Shengyuan
Abstract : Abstract: The aim of this study was to investigate the clinical characteristics of central nervous system (CNS) aspergillosis in immunocompetent patients. This study enrolled six immunocompetent patients diagnosed with CNS aspergillosis. Additionally, we reviewed the clinical profiles for 28 cases reported in the literature. The age, gender, etiology of Aspergillus infection, clinical manifestations, location of the lesion, treatment, and prognosis were analyzed. There were 19 men (average age, 54.6 ± 14.3 years) and 15 women (average age, 47.0 ± 19.4 years). The clinical manifestations included headache (55.9%; n = 19), visual impairment (32.4%; n = 11), diplopia (32.4%; n = 11), hemiplegia (20.6%; n = 7), fever (17.6%; n = 6), and epilepsy (8.8%; n = 3). According to the radiological features, CNS aspergillosis lesions were divided into two subtypes: parenchymal lesions in the cerebral lobes (n = 11), and meningeal lesions in the meninges (n = 23). The patients with meningeal lesions are easy to be complicated with more serious cerebrovascular diseases, such as subarachnoid hemorrhage and massive infarction. Most of the lesions in brain parenchyma were abscess formation, and magnetic resonance imaging showed ring enhancement. The clinical diagnosis of Aspergillus infection was mainly based on brain biopsy (n = 14), autopsy (n = 8), pathological examination of adjacent brain tissues (n = 7), cerebrospinal fluid (CSF) or tissue culture (n = 3), and second-generation sequencing analysis of the CSF (n = 3). Clinical improvement was achieved in 23 cases, and 11 patients succumbed to the disease. Voriconazole treatment was effective in 24 (70.6%) cases. Immunocompetent subjects are also at risk for Aspergillus infections. Concomitant cerebrovascular diseases are common in patients with CNS aspergillosis, especially in patients with meningeal aspergillosis. Parenchymal aspergillosis lesions are usually localized and manifest as brain abscesses with annular enhancement on magnetic resonance imaging. Biopsy, CSF culture, and next-generation sequencing are mainstream diagnostic modalities. Voriconazole is an effective treatment for Aspergillus infection, and early diagnosis and treatment should be highlighted.